THE IMPACT OF MOBILE FINANCIAL SERVICES ON THE USAGE DIMENSION OF FINANCIAL INCLUSION: AN EMPIRICAL STUDY FROM BANGLADESH - Md Ali Ashraf, (Copernican Journal of Finance & Accounting, 2022)
A plethora of studies have investigated how Mobile Financial Services (MFS) induces financial inclusion around the world. However, research in the context of Bangladesh was rather limited. Hence, the primary objective of this paper was to investigate whether there was a statistically significant relationship between MFS and financial inclusion, measured by two time series variables – the number of MFS agents and number of registered MFS users per 100,000 of population, from 2017 to 2020. For analyzing the relationship between these two variables, multiple statistical methods were employed – including Vector Auto Regression, Cointegration and Granger Causality. The analysis revealed that both time series variables had an increasing trend with time. More importantly, the analysis specified that there was no statistically significant relationship between MFS, measured by the number of agents and the ‘usage’ dimension of financial inclusion, measured by number of registered MFS users in the context of Bangladesh. Moreover, the study was unable to find any significant changes in the trends of these variables that could be attributed to the COVID-19 pandemic in Bangladesh.